PENGARUH VARIASI KONSENTRASI SODIUM DODECYL SULFATE (C12H25NaSO4) TERHADAP MORFOLOGI PERMUKAAN PADA PEMBENTUKAN LAPISAN TIPIS KOMPOSIT Ni-TiAlN DENGAN METODE ELEKTRODEPOSISI - Yulia Ermadiana; Esmar Budi; Iwan Sugihartono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Has been done a coating process of the thin composite Ni-TiAlN to review the effect of variations concentration Sodium Dodecyl Sulfate (C12H25NaSO4) on the surface morphology of thin layer composite Ni-TiAlN. This coating process was using electrodeposition method with a current 0.45Î¼A, voltage 45mV for 15 minutes. This composite was formed on a Tungsten Carbide substrate with solution composition of the electrolyte which consists of 2 gr/l AlN, 2 gr/l TiN, 0.49 Mol/l H3BO3, 0.17 M NiCl26H2O, 0.38 M NiSO46H2O and Sodium Dodecyl Sulfate (C12H25NaSO4). The variation concentration of Sodium Dodecyl Sulfate (C12H25NaSO4) that used are 0,2 g/l, 0.4 g/l and 0.6 g/l. This research uses characterization of Scanning Electron Microscopy (SEM) which showed that the bigger of concentration variation of Sodium Dodecyl Sulfate (C12H25NaSO4) make the surface morphology of thin layers composite Ni-TiAlN formed smoother than lower concentration, the smaller of aggregate and the crack are seen more clearly.